Territórios, rizomas e o curriculo na escola - DINIZ, Francisco Perpetuo Santos (2013)
This article discursses the possibility of thinking the formal school's curriculum from the perspective of formation of a rhizome-territory, that is, a flexible study proposal, non-hierarquical, interdisciplinary, and based on educational on educational practices oriented as to confront the dominant disciplinary education model. Firstly, Deleuze and Guattari's concepts of territory and rhizome are presented in order to set basis for the notion of territory and curriculum within the context of the Sciences of Education. Next, the curriculum is discussed as possibility for the integration of knowledges, experiences, educational practices to be developed in formal schooling regarding citzenship political awareness, and social transformation. Finally, in the analysis the considers the curriculum in a holistic context, critical, flexible, rhizomatic, interdisciplinary, opened to the possibilities of new educational doings.